PENGARUH JUMLAH KUNJUNGAN WISATAWAN, JUMLAH OBJEK WISATA DAN JUMLAH HOTEL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA PROVINSI BALI - Novita Sari, Dian Ayu; Urmila Dewi, Made Heny (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Tourism is a regional superior potential that has all the attractions, including natural scenery, oceans, mountains, traditions, arts and culture that can attract both domestic and foreign tourists to visit and have a positive impact on regional development. This study aims to analyze the effect of the number of tourist visits, the number of tourist attractions, and the number of hotels simultaneously and partially on local revenue in regencies / cities in Bali Province. The data used in this research is secondary data, namely by observing related documents or data sources. The population used in this research is the entire number of tourist visits, the number of tourist objects, the number of hotels, and local revenue in regencies / cities in Bali Province, with the number of samples used in the five years 2014-2018 period used in this study, namely the number of tourist visits, the number of tourist objects, the number of hotels and local revenue in the regencies / cities of Bali Province. The analysis technique used is multiple linear regression. The results showed that the number of tourist visits both domestic and foreign, the number of tourist objects, and the number of hotels simultaneously affect the local revenue of districts / cities in Bali Province. The number of tourist visits both domestic and foreign, the number of tourist objects, and the number of hotels partially have a positive and significant effect on local revenue in regencies / cities of Bali Province Keywords : number of tourist visits, number of tourist objects, number of hotels, local revenue (PAD)